The flocculation of silica suspensions using gelatine - Fabile, Teresita S. (1973)
Using refiltration experiments, a detailed study has been made on the flocculation of silica particles with gelatine with relation to the amount of gelatine and the pH. The efficiency of flocculation is dependent on the amount of gelatine used. At high gelatine concentrations, there is little flocculation. The best flocculations are obtained when the gelatine is 250 p.p.m. The efficiency of flocculation is also very pH-dependent. With a negatively charged suspension, the best flocculation is obtained under pH conditions where the gelatine molecules carry a small positive charge.
The experimental results fit the Smellie-La Mer-Healy modified theoretical equations for flocculation at low gelatine concentrations. At high gelatine concentrations, the S-L-H model predicts very much higher refiltration rates that actual experimental values. This discrepancy is possibly due to the interactions between extended segments of the gelatine molecule which is not considered in the S-L-H model.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Flocculation; Gelatin; Silica